Changes in the bending modulus of AOT based microemulsions induced by the incorporation of polymers in the water core. Issue 30 (15th July 2016) - Kuttich, Björn; Grefe, Ann-Kathrin; Stühn, Bernd
Abstract : The bending modulus κ is known to be a crucial parameter for the stability of the droplet phase. By combination of droplet radii and percolation temperature T p it is found to increase under the addition of polymer, if the correct droplet radii at T p are considered. Abstract : The bending modulus κ is known to be a crucial parameter for the stability of the droplet phase in microemulsion systems. For AOT based water in oil microemulsions the bending modulus of the surfactant has values close to k B T but can be influenced by the presence of polymers. In this work we focus on the water soluble polymer polyethylene glycol and how it influences the bending modulus. An increase by a factor of three is found. For the correct evaluation of the bending modulus via percolation temperatures and droplet radii, thus by dielectric spectroscopy and small angle X-ray scattering, the determination of the radii right at the percolation temperature is crucial as we will show, although it is often neglected. In order to precisely determine the droplet radii we will present a global fitting model which provides reliable results with a minimum number of free fitting parameters.